The Employee Experience - Maylett, Tracy; Wride, Matthew (Ascent Audio, 2019)
Want a profit-enhancing Customer Experience? Start with the Employee Experience. The Employee Experience helps organizations attract and retain top talent, and reveals the secrets for building a deeply engaged workforce. With insights into the dynamics of trust and mutual expectations, this book proves that before you can deliver a transcendent customer experience (CX), you must first build a superlative employee experience (EX). It's not about perks. It's not about creating a worker's utopia, and it doesn't mean that work must be easy; employees are responsible for managing expectations and meeting the organization's requirements. But by establishing a clear set of expectations and promises-collectively known as "the Contract"-and upholding it consistently, employers can build the essential trust that leads to powerful employee engagement. The data are unambiguous: organizations with engaged workforces are more profitable, enjoy greater growth, and win the battle to keep the most talented personnel. Employees who have a fulfilling, rewarding work experience perform better, achieve more, and bring more value to the organization. The Employee Experience teaches you how to leverage the full potential of your people to transform your future.